Incidence of recurrence and development of polypoidal lesions following half-dose and two-thirds dose photodynamic therapy for pachychoroid neovasculopathy - Koji Tanaka; Hajime Onoe; Keigo Takeshima; Michiteru Kono; Yu Wakatsuki; Akiyuki Kawamura; Ryusaburo Mori; Hiroyuki Nakashizuka (Scientific Reports)
Abstract The purpose of this study was to determine the recurrence rate, factors, incidence of polypoidal lesions, and risk factors for developing polypoidal lesions after a reduced dose photodynamic therapy (PDT) for pachychoroid neovasculopathy (PNV) without polypoidal lesions. This study is an observational case-control study. The study included 105 patients (77 men, 28 women; mean age, 61.6 years) with PNV in 105 eyes treated with reduced PDT. Twenty-eight eyes were treated with half-dose PDT and 77 eyes with two-thirds dose PDT, with an average follow-up of 588 days. Logistic regression analysis was used to examine factors of recurrence and polypoidal lesions. Recurrence was observed in six patients (21%) receiving half-dose PDT and 24 patients (31%) receiving two-thirds dose PDT. Polypoidal lesions developed in seven patients (7%). Recurrence factors were duration of follow-up (P < 0.0001), macular neovascularization (MNV) thickness before PDT (P = 0.010), and age (P = 0.002). MNV area before PDT was an independent risk factor for the development of polypoidal lesions (P = 0.001). Long-term follow-up after reduced PDT for PNV is necessary because recurrence factors include follow-up duration, age, and MNV thickness. A risk factor for polypoidal lesions after PNV treatment was the MNV area before PDT.